Motor vehicle tax service satisfaction moderated by “SAMSAT CAR” service - Tambunan, Dennis Rydarto; Reza, Heru Kreshna; Yustanti, Nirta Vera; Herfianti, Meiffa; Susanti, Melly (Journal of Economics and Business Letters, 2022)
One-Stop Service System (SAMSAT CAR) is one of  the government agencies that provides services to the public/community related to the payment of motor vehicle taxes. Samsat has provided services to taxpayers who want to pay Motorized Vehicle Tax (PKB) through facilities such as the provision of several vehicles called “SAMSAT CAR”. The reason for this review was to decide the impact of administration on citizen fulfillment prior and then afterward the SAMSAT Vehicle administration. This review utilizes an expressive technique with a quantitative methodology. The sample selection technique used by the author in this study is non-probability sampling. The selected population is Bengkulu City residents, the sample is 100 taxpayers who have made vehicle tax payments, subject in this study is the SAMSAT CAR (SAMLING). The data was processed using the IBM SPSS Statistics 22 tool assisted by the Ms. Excel. The consequences of this review are that before the SAMSAT Vehicle administration strategy was carried out, citizen fulfillment was just 41.9%. With the directing variable (SAMLING) it can reinforce the impact of the Help variable (X1) on Citizen Fulfillment (Y). SAMLING (SAMSAT Vehicle) has expanded local area fulfillment, particularly citizens in Bengkulu City. In view of the aftereffects of various direct relapse, it very well may be presumed that the "Theory is Acknowledged" so one might say that the presence of a directing variable or SAMLING can reinforce or build the impact of the Citizen Fulfillment variable